Effectiveness of health education intervention in improving knowledge, attitude, and practices regarding tuberculosis among HIV patients in General Hospital Minna, Nigeria – a randomized control trial - Bisallah, Chindo Ibrahim; Gyanchand Rampal, Lekhraj Rampal; Lye, Munn Sann; Mohd Sidik, Sherina; Ibrahim, Normala; Iliyasu, Zubairu; Onyilo, Michael Ochigbo (Public Library of Science, 2018)
Introduction: The risk of development of active TB in HIV-infected individuals is 20–37 times higher than those that are HIV negative. Poor knowledge of TB amongst people living with HIV has been associated with high transmission. Objectives: To determine the effectiveness of a new health education intervention module in improving knowledge, attitude, and practice (KAP) regarding tuberculosis among HIV patients in General Hospital Minna, Nigeria. Methods: A randomized control trial was carried out from July 2015 to June 2017. A random number generating program was used to allocate 226 respondents into 2 groups. The intervention group received health education regarding tuberculosis using the developed module. The control group received the normal services provided for HIV patients. Data were collected from December 2015 to September 2016 at baseline, immediate post intervention, three, six and nine months. The outcome measures were knowledge, attitude, and practice. Results: There was no significant difference with respect to socio-demographic characteristics, KAP of the respondents in the intervention and control group at baseline. However, there was significant improvement in knowledge in the intervention group compared to the control group, group main effect (F = (1,218) = 665.889, p = 0.001, partial ἠ2 = 0.753, d = 5.4); time (F = (3.605, 218) = 52.046, p = 0.001, partial ἠ2 = 0.193, d = 1.52) and interaction between group with time (F = (3.605, 218) = 34.028, p = 0.001, partial ἠ2 = 0.135, d = 1.23). Likewise, there was significant improvement in attitude, group main effect (p = 0.001, d = 1.26) and time (p = 0.001, p, d = 0.65). Similarly, there was improvement in practice, group main effect, time, and interaction of group with time (p < 0.05). Conclusion: The health education intervention program was effective in improving KAP regarding tuberculosis among HIV patients.